Minimal processing of iceberg lettuce has no substantial influence on the survival, attachment and internalization of E. coli O157 and Salmonella - Van der Linden, Inge (2016)
Fil: Van der Linden, Inge. Universidad de Gante. Facultad de Ingeniería en Biociencias; Bélgica.